A New Anthraquinone From the Root Bark of Cassia nodosa - Yadava, N.K.; Singh, B.K.; Kumar, A. (Asian Journal of Chemistry, 2010)
The present communication deals with the isolation andstructural elucidation of 1,8-dihydroxy-6,7-dimethoxy-2-methylanthraquinone isolated from the root bark of Cassia nodosa Buch.Ham, a medicinal plant.